Understating the Impact of Economic Factors on Stock Yield: Jordanian Stock Market Case - Al-Nimri, Ade; Altarawneh, Yaseen (International Journal of Economics and Financial Issues, 2020)
The study aimed to identify the most salient and critical factors influencing the Stock yield and causing this sharp fluctuation, and clarifying which factors are more influential than others on the Stock yield in the Amman Stock Market – Jordan. The study population consisted of all listed companies in the Amman Stock Market. The sample of the study is random stratified and includes 30% of the original population. The study sample numbered 60 companies of the companies listed on the Amman Stock Market. The main findings are the positive relationship between inflation rates, interest rate, number of employees and capital shares with income shares. The results also showed no relationship between the deficit and surplus of balance of payments and stock yield, as well as no relationship between the level of gross domestic product (GDP) and the stock yield in Amman Stock Market in Jordan. Keywords: Stock yield, inflation rate, interest rate, number of employees, balance of payment, gross domestic product. JEL Classifications: E44; G10 DOI: https://doi.org/10.32479/ijefi.10415